La Lucha for Cuba : Religion and Politics on the Streets of Miami - De La Torre, Miguel A. (Book collections on Project MUSE., 2003)
For many in Miami's Cuban exile community, hating Fidel Castro is as natural as loving one's children. This hatred, Miguel De La Torre suggests, has in fact taken on religious significance. In La Lucha for Cuba, De La Torre shows how Exilic Cubans, a once marginalized group, have risen to power and privilege--distinguishing themselves from other Hispanic communities in the United States--and how religion has figured in their ascension.